Synergistic effects of overweight/obesity and high hemoglobin A1c status on elevated high-sensitivity C-reactive protein in Chinese adults: a cross-sectional study - Shen, Qianqian; He, Tingchao; Li, Ting; Szeto, Ignatius Man-Yau; Mao, Shuai; Zhong, Wuxian; Li, Pin; Jiang, Hua; Zhang, Yumei (Frontiers in Nutrition, 2023)
Background High-sensitivity C-reactive protein (hs-CRP) is an inflammatory marker that has been suggested as a predictor of cardiovascular diseases. High glycated hemoglobin (HbA1c) levels and overweight/obesity are independently associated with elevated hs-CRP; meanwhile, high HbA1c levels are frequently accompanied by overweight or obesity. However, their joint effect on elevated hs-CRP levels has not been well-established. Therefore, we evaluated whether overweight/obesity modified the association between high HbA1c levels and elevated hs-CRP. Methods Based on cross-sectional data from the Chinese Urban Adults Diet and Health Study (CUADHS) in 2016, we included 1,630 adults aged 18–75 years (mean age 50.16 years and 33.6% male). Elevated hs-CRP was defined as serum hs-CRP ≥ 3 and <10 mg/L. The interactive effects of BMI and HbA1c levels on the risk of elevated hs-CRP levels were calculated by using multiple logistic regression models, followed by strata-specific analyses. Results Individuals with elevated hs-CRP had a higher rate of HbA1c level than those without elevated (25.3 vs. 11.3%, P < 0.001), as well as a higher rate of overweight/obesity (67.1 vs. 43.5%, P < 0.001). Higher HbA1c levels were independently associated with an increased risk of elevated hs-CRP [adjusted odds ratio (aOR) = 2.31, 95% confidence interval (CI): 1.47, 3.65], as well as overweight/obesity with the risk of elevated hs-CRP (aOR = .31, 95% confidenc–3.73). Furthermore, overweight/obesity showed a significant synergistic effect on high HbA1c levels with a higher aOR of 5.25 (2.77, 9.95) (Pinteraction < 0.001). This synergistic effect was more prominent when stratified by age (in 18–44 years old, aOR, 95% CI = 30.90, 4.40–236.47 for interaction vs. 6.46, 1.38–30.23 for high HbA1c only) and gender (in women, aOR, 95% CI = 8.33, 3.80–18.23 for interaction vs. 2.46,1.38–4.40 for high HbA1c only). Conclusion There are synergistic effects of high HbA1c levels and overweight/obesity on the risk of elevated hs-CRP in Chinese adults, with more significant effects in adults aged 18–44 years or females. Intervention strategies for preventing high blood glucose levels and body weight simultaneously may be important for reducing hs-CRP-related diseases. Further studies are needed to confirm this finding in other populations, and its molecular mechanisms need to be elucidated.